The Significance of Translation History – A Roundtable Discussion - Hermans, Theo; Rundle, Christopher (chronotopos – A Journal of Translation History, 2022)
In 2021, the Vienna Doctoral Summer School on Translation History took place for the fourth time. At the halfway point of the summer school – on a Sunday in September 2021 – two of the summer school professors – Christopher Rundle and Theo Hermans – met to discuss the question: Why do we do translation history at all? The conversation was led by Tomasz Rozmysłowicz and Julia Richter.